Composite material for lightweight rail transit bridge and forming process of composite material

A composite material for rail transit bridges, enhanced by modified carbon fibers and a heat-resistant agent, addresses brittleness and processing issues, providing improved toughness and thermal stability for enhanced durability and safety.

CN119220029AActive Publication Date: 2024-12-31江苏悦圣亚电气有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411444076.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2024-12-31
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

Existing polymer alloy cable trays for rail transit bridges suffer from brittleness, insufficient energy absorption, poor processing performance, and limited high-temperature resistance, hindering their development and application in demanding conditions.

Method used

A composite material is developed by modifying carbon fibers with dopamine self-polymerization and hyperbranched epoxy resin, combined with a heat-resistant agent, to enhance toughness, mechanical properties, and thermal stability through a specific molding process involving ultraviolet irradiation and extrusion.

Benefits of technology

The composite material achieves improved impact resistance, durability, and high-temperature performance, ensuring the safety and longevity of rail transit bridges under extreme conditions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of composite materials, in particular to a composite material for a lightweight rail transit bridge and a forming process of the composite material. The preparation method comprises the following steps: uniformly mixing modified carbon fibers, a heat-resistant agent and a photoinitiator, and performing ultraviolet irradiation to obtain a compound; uniformly mixing polyvinyl chloride resin, an acrylonitrile-butadiene-styrene copolymer, the compound, a plasticizer, an antioxidant, a stabilizer and a lubricant, and internally mixing in an internal mixer at the internal mixing temperature of 165-175 DEG C to obtain a blend; and finally, adding the blend into a double-screw extruder, and carrying out extrusion granulation to obtain the composite material. The composite material prepared by the invention has excellent heat resistance and mechanical properties, and can effectively meet the use requirements of lightweight rail transit bridges.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a composite material for a lightweight rail transit bridge and a molding process thereof. Background Art

[0002] Rail transit bridge is an important part of the urban rail transit system, mainly used to support and protect cables, wires, etc., to ensure the stable transmission of power and signals. With the continuous development of cable tray wiring technology at home and abroad, in addition to traditional steel cable trays, cable trays made of other materials are also being developed, such as stainless steel, aluminum alloy, fiberglass, color steel, etc.

[0003] In recent years, a new type of cable tray made of polymer alloy material has gradually entered the market. The polymer alloy cable tray is upgraded on the basis of the basic structure of the traditional cable tray, changing the single-layer structure of the traditional cable tray, combining the plastic extrusion process, using polymer resin and a variety of fine chemical additives, and manufactured through plastic modification and extrusion process of special equipment and molds. This new type of cable tray not only retains the bearing capacity of the traditional cable tray, but also has the excellent insulation, flame retardant and corrosion resistance of plastic products, extending the service life. However, the existing polymer alloy cable tray can meet the use requirements in terms of strength and rigidity, but its brittleness is relatively large. When facing instantaneous impact, the energy absorption capacity is insufficient, resulting in a short board in toughness; at the same time, the processing performance of polymer materials is poor, and the differences in different phase interfaces in the alloy material system further increase the difficulty of processing; in addition, under special working conditions, the insufficient high temperature resistance of this material also limits the further development of polymer alloy cable trays.

[0004] Therefore, we propose a composite material for lightweight rail transit bridge and its molding process. Summary of the invention

[0005] The object of the present invention is to provide a composite material for a lightweight rail transit bridge and a molding process thereof, so as to solve the problems raised in the prior art.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A molding process of a composite material for a lightweight rail transit bridge comprises the following steps:

[0008] Step S1: uniformly mixing the modified carbon fiber, the heat-resistant agent and the photoinitiator, and irradiating the mixture with ultraviolet light to obtain a composite;

[0009] Step S2: uniformly mixing the polyvinyl chloride resin, acrylonitrile-butadiene-styrene copolymer, the compound, the plasticizer, the antioxidant, the stabilizer, and the lubricant, and performing internal mixing in an internal mixer at a temperature of 165-175° C. to obtain a blend;

[0010] Step S3: adding the blend obtained in S2 into a twin-screw extruder for extrusion granulation to obtain a composite material.

[0011] Furthermore, in step S1, the composite comprises the following components by weight: 3-8 parts of modified carbon fiber, 2-7 parts of heat-resistant agent, and 0.5-1.0 parts of photoinitiator.

[0012] Furthermore, the preparation method of the modified carbon fiber is as follows:

[0013] Step (1): placing the carbon fiber in acetone, extracting for 44-48 hours, washing and drying to obtain pretreated carbon fiber;

[0014] Step (2): adjust the pH of Tris-HCl buffer to 8.5, add dopamine hydrochloride and polyethyleneimine and mix evenly, then add pretreated carbon fiber and mix evenly, react for 22-24 hours, wash and dry to obtain amino carbon fiber;

[0015] Step (3): under nitrogen protection, trimethylolpropane triglycidyl ether, 2,2'-diallyl bisphenol A and tetrabutylammonium bromide are uniformly mixed, reacted at 75-85° C. for 22-24 hours, cooled to room temperature, dissolved, layered, rotary evaporated and dried to obtain a hyperbranched epoxy resin;

[0016] Step (4): Evenly mix the amino carbon fiber and the hyperbranched epoxy resin, and react at 30-40° C. for 8-10 hours to obtain modified carbon fiber.

[0017] Furthermore, in the step (1), the mass ratio of carbon fiber to acetone is 1:(20-40).

[0018] Furthermore, in step (2), the concentration of Tris-HCl buffer is 0.01 mol / L, and the mass ratio of dopamine hydrochloride, polyethyleneimine and Tris-HCl buffer is 1:(1-2):(300-500).

[0019] Furthermore, in step (2), the mass of the pretreated carbon fiber is 6-8 times the mass of dopamine hydrochloride.

[0020] Furthermore, in step (3), the mass ratio of trimethylolpropane triglycidyl ether, 2,2'-diallyl bisphenol A and tetrabutylammonium bromide is 1:(1.2-1.5):(0.1-0.3).

[0021] Furthermore, in the step (4), the mass ratio of the amino carbon fiber to the hyperbranched epoxy resin is 1:(1-2).

[0022] Furthermore, the preparation method of the heat-resistant agent is as follows:

[0023] Mix L-cysteine, 1,2,4-cyclohexanetricarboxylic anhydride and glacial acetic acid evenly, stir at room temperature for 22-24 hours, heat to 110-120°C and reflux for reaction for 4-6 hours, and obtain an intermediate after vacuum distillation, washing and drying; mix the intermediate, 2-bis[4-(4-aminophenoxy)phenyl]propane and tetrabutylammonium bromide evenly, heat to 50-70°C, add triphenyl phosphite and aniline, continue to heat to 110-120°C, react for 1-2 hours, and obtain a heat-resistant agent after precipitation, filtration and drying.

[0024] In the above technical scheme, the amino group in L-cysteine ​​reacts with the anhydride group of 1,2,4-cyclohexanetricarboxylic anhydride to first form amide acid at room temperature, and then refluxes to react and remove water to complete imidization, thereby obtaining an imide-containing diacid monomer, i.e., an intermediate; then, the intermediate reacts with two amino groups of 2-bis[4-(4-aminophenoxy)phenyl]propane, and aniline is used as a monofunctional end-capping agent to adjust the molecular weight, thereby obtaining a thiol-containing polyamide-imide, i.e., a heat-resistant agent.

[0025] Furthermore, the mass ratio of L-cysteine, 1,2,4-cyclohexanetricarboxylic anhydride and glacial acetic acid is 1:(1.6-1.8):(40-50).

[0026] Furthermore, the mass ratio of the intermediate, 2-bis[4-(4-aminophenoxy)phenyl]propane and tetrabutylammonium bromide is 1:(1.0-1.5):(2.0-2.2).

[0027] Furthermore, the mass of the triphenyl phosphite is 3.0-3.5 times the mass of the intermediate, and the mass of the aniline is 2-3 times the mass of the intermediate.

[0028] Furthermore, in step S1, the photoinitiator is 2,2-dimethoxy-2-phenylacetophenone.

[0029] Furthermore, in step S1, the ultraviolet irradiation process conditions are: irradiation with 360-400nm ultraviolet rays for 20-50min, and irradiation intensity of 20-35mW / cm 2 .

[0030] Further, the composite material comprises the following components by weight:

[0031] 80-100 parts of polyvinyl chloride resin, 10-20 parts of acrylonitrile-butadiene-styrene copolymer, 5-15 parts of compound, 2-10 parts of plasticizer, 0.2-0.5 parts of antioxidant, 5-15 parts of stabilizer and 0.5-1.0 parts of lubricant.

[0032] Furthermore, the plasticizer is dioctyl phthalate.

[0033] Furthermore, the antioxidant is antioxidant 1010.

[0034] Furthermore, the stabilizer is a composite calcium-zinc stabilizer.

[0035] Furthermore, the lubricant is stearic acid.

[0036] Furthermore, in step S2, the working temperature of the extrusion granulation is 170-180°C.

[0037] An application of a composite material for a lightweight rail transit bridge frame comprises the following steps: feeding the composite material into an injection molding machine, melting it at 165-175° C., injecting it into a mold, and cooling it to obtain a lightweight rail transit bridge frame.

[0038] Furthermore, the process conditions of the mold are: mold temperature 180-185° C., and mold pressure 10-30 MPa.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] 1. A composite material for a lightweight rail transit bridge and a molding process thereof of the present invention utilizes dopamine self-polymerization to generate polydopamine and attach it to the surface of carbon fiber. Polydopamine can be used as a platform for secondary reactions. Polyethyleneimine is grafted to the surface of carbon fiber through copolymerization. The surface of carbon fiber is covered with grafted polymer, which significantly increases the active amino groups on the surface and improves the surface roughness.

[0041] Then, trimethylolpropane triglycidyl ether and 2,2'-diallyl bisphenol A were used as reaction monomers, and tetrabutylammonium bromide was used as a reaction catalyst to synthesize a hyperbranched epoxy resin with terminal allyl groups through chemical reactions. Among them, trimethylolpropane triglycidyl ether has three functional epoxy groups, and the main chain is short and the side chains are more, which gives the molecular chain good flexibility. It can not only effectively toughen carbon fibers, but also improve their mechanical properties and enhance the impact resistance and durability of the material; 2,2'-diallyl bisphenol A not only has two functional terminal allyl groups, but also contains a conjugated symmetrical molecule with two benzene rings, which enhances the rigidity of the molecular chain and improves the thermal properties of the material.

[0042] Finally, strong chemical crosslinking is formed by reacting the amino carbon fibers with the epoxy groups of the hyperbranched epoxy resin, which not only improves the interfacial bonding strength between the carbon fibers and the resin matrix, but also improves the mechanical properties and thermal stability of the material.

[0043] 2. A composite material for a lightweight rail transit bridge and its molding process of the present invention, through the reaction of the amino group in L-cysteine ​​and the anhydride group of 1,2,4-cyclohexanetricarboxylic anhydride, obtains an imide-containing diacid monomer, i.e., an intermediate; then the intermediate reacts with the two amino groups of 2-bis[4-(4-aminophenoxy)phenyl]propane to obtain a thiol-containing polyamide-imide, i.e., a heat-resistant agent, which can further undergo a thiol-ene click reaction with the double bonds in the modified carbon fiber to form a composite. Adding the composite to the preparation process of the composite material significantly improves the toughness and strength of the composite material, thereby meeting the requirements of the rail transit bridge for lightweight and high strength. At the same time, the excellent heat resistance and chemical stability of the composite material greatly extend its service life under extreme working conditions, providing effective protection for the safety and economy of the rail transit system. DETAILED DESCRIPTION

[0044] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] In this embodiment, polyvinyl chloride resin: brand SG-5, sourced from Yuyao Chengfeng Plastics Co., Ltd.; acrylonitrile-butadiene-styrene copolymer: brand PA-747, sourced from Taiwan Chi Mei Industrial Co., Ltd.; antioxidant 1010: industrial grade, sourced from BASF AG; composite calcium zinc stabilizer: model ZP-510, sourced from Shanghai Zirun Chemical Additives Co., Ltd.; carbon fiber: T700 chopped carbon fiber, 3-5 mm long, sourced from Shanghai Lishuo Composite Materials Technology Co., Ltd.

[0046] In the following examples and comparative examples, 1 part is equal to 10 g.

[0047] Embodiment 1: A molding process of a composite material for a lightweight rail transit bridge, comprising the following processes:

[0048] Step S1: 3 parts of modified carbon fiber, 2 parts of heat-resistant agent and 0.5 parts of photoinitiator were mixed evenly, and irradiated with 360nm ultraviolet light for 20min, with an irradiation intensity of 20mW / cm 2 , to obtain a complex;

[0049] Step S2: 80 parts of polyvinyl chloride resin, 10 parts of acrylonitrile-butadiene-styrene copolymer, 5 parts of the composite, 2 parts of dioctyl phthalate, 0.2 parts of antioxidant 1010, 5 parts of composite calcium zinc stabilizer, and 0.5 parts of stearic acid are mixed uniformly, and kneaded in an internal mixer at a kneading temperature of 165° C. to obtain a blend;

[0050] Step S3: adding the blend obtained in S2 into a twin-screw extruder, and extruding and granulating at a working temperature of 170° C. to obtain a composite material;

[0051] The preparation method of modified carbon fiber is as follows:

[0052] Step (1): 3 parts of carbon fiber are placed in 60 parts of acetone, extracted for 44 hours, and after washing and drying, a pretreated carbon fiber is obtained;

[0053] Step (2): adjusting 150 parts of 0.01 mol / L Tris-HCl buffer to pH=8.5, adding 0.5 parts of dopamine hydrochloride and 0.5 parts of polyethyleneimine and mixing evenly, then adding 3 parts of pretreated carbon fiber and mixing evenly, reacting for 22 hours, washing and drying, and obtaining amino carbon fiber;

[0054] Step (3): Under nitrogen protection, 3 parts of trimethylolpropane triglycidyl ether, 3.6 parts of 2,2'-diallyl bisphenol A and 0.3 parts of tetrabutylammonium bromide are mixed evenly, reacted at 75°C for 22 hours, cooled to room temperature, dissolved, layered, rotary evaporated and dried to obtain a hyperbranched epoxy resin;

[0055] Step (4): 3 parts of amino carbon fiber and 3 parts of hyperbranched epoxy resin were mixed evenly, and reacted at 30° C. for 8 hours to obtain modified carbon fiber;

[0056] The preparation method of the heat-resistant agent is as follows:

[0057] 2 parts of L-cysteine, 3.2 parts of 1,2,4-cyclohexanetricarboxylic anhydride and 80 parts of glacial acetic acid were mixed evenly, stirred at room temperature for 22 hours, heated to 110°C and refluxed for reaction for 4 hours, and distilled under reduced pressure, washed and dried to obtain an intermediate; 2 parts of the intermediate, 2 parts of 2-bis[4-(4-aminophenoxy)phenyl]propane and 4 parts of tetrabutylammonium bromide were mixed evenly, heated to 50°C, 6 parts of triphenyl phosphite and 4 parts of aniline were added, and the temperature was continued to be raised to 110°C, reacted for 1 hour, and a heat-resistant agent was obtained after precipitation, filtration and drying;

[0058] An application of a composite material for a lightweight rail transit bridge comprises the following steps: feeding the composite material into an injection molding machine, melting it at 165° C., injecting it into a mold (mold temperature 180° C., mold pressure 10 MPa), and cooling it to obtain a lightweight rail transit bridge.

[0059] Embodiment 2: A molding process of a composite material for a lightweight rail transit bridge, comprising the following processes:

[0060] Step S1: 5 parts of modified carbon fiber, 5 parts of heat-resistant agent and 0.8 parts of photoinitiator were mixed evenly, and irradiated with 380nm ultraviolet light for 30min, with an irradiation intensity of 30mW / cm 2 , to obtain a complex;

[0061] Step S2: 90 parts of polyvinyl chloride resin, 15 parts of acrylonitrile-butadiene-styrene copolymer, 10 parts of the composite, 5 parts of dioctyl phthalate, 0.3 parts of antioxidant 1010, 10 parts of composite calcium zinc stabilizer, and 0.8 parts of stearic acid are mixed uniformly, and kneaded in an internal mixer at a kneading temperature of 170° C. to obtain a blend;

[0062] Step S3: adding the blend obtained in S2 into a twin-screw extruder, and extruding and granulating at a working temperature of 175° C. to obtain a composite material;

[0063] The preparation method of modified carbon fiber is as follows:

[0064] Step (1): 5 parts of carbon fiber are placed in 150 parts of acetone, extracted for 46 hours, and after washing and drying, a pretreated carbon fiber is obtained;

[0065] Step (2): adjusting 280 parts of 0.01 mol / L Tris-HCl buffer to pH=8.5, adding 0.7 parts of dopamine hydrochloride and 1 part of polyethyleneimine and mixing evenly, then adding 5 parts of pretreated carbon fiber and mixing evenly, reacting for 23 hours, washing and drying, and obtaining amino carbon fiber;

[0066] Step (3): Under nitrogen protection, 8 parts of trimethylolpropane triglycidyl ether, 10 parts of 2,2'-diallyl bisphenol A and 1.6 parts of tetrabutylammonium bromide are mixed evenly, reacted at 80°C for 23 hours, cooled to room temperature, dissolved, layered, rotary evaporated and dried to obtain a hyperbranched epoxy resin;

[0067] Step (4): 5 parts of amino carbon fiber and 7.5 parts of hyperbranched epoxy resin were mixed evenly, and reacted at 35° C. for 9 hours to obtain modified carbon fiber;

[0068] The preparation method of the heat-resistant agent is as follows:

[0069] 5 parts of L-cysteine, 8.5 parts of 1,2,4-cyclohexanetricarboxylic anhydride and 250 parts of glacial acetic acid were mixed evenly, stirred at room temperature for 23 hours, heated to 115°C and refluxed for reaction for 5 hours, and distilled under reduced pressure, washed and dried to obtain an intermediate; 5 parts of the intermediate, 6 parts of 2-bis[4-(4-aminophenoxy)phenyl]propane and 10.5 parts of tetrabutylammonium bromide were mixed evenly, heated to 60°C, 16.5 parts of triphenyl phosphite and 12.5 parts of aniline were added, and the temperature was continued to be raised to 115°C, reacted for 1.5 hours, and a heat-resistant agent was obtained after precipitation, filtration and drying;

[0070] An application of a composite material for a lightweight rail transit bridge comprises the following steps: feeding the composite material into an injection molding machine, melting it at 170°C, injecting it into a mold (mold temperature 182°C, mold pressure 20Mpa), cooling it, and obtaining a lightweight rail transit bridge.

[0071] Embodiment 3: A molding process of a composite material for a lightweight rail transit bridge, comprising the following processes:

[0072] Step S1: 8 parts of modified carbon fiber, 7 parts of heat-resistant agent and 1.0 part of photoinitiator were mixed evenly, and irradiated with 400nm ultraviolet light for 50min, with an irradiation intensity of 35mW / cm 2 , to obtain a complex;

[0073] Step S2: 100 parts of polyvinyl chloride resin, 20 parts of acrylonitrile-butadiene-styrene copolymer, 15 parts of the composite, 10 parts of dioctyl phthalate, 0.5 parts of antioxidant 1010, 15 parts of composite calcium zinc stabilizer, and 1.0 parts of stearic acid are mixed uniformly, and kneaded in an internal mixer at a kneading temperature of 175° C. to obtain a blend;

[0074] Step S3: adding the blend obtained in S2 into a twin-screw extruder, and extruding and granulating at a working temperature of 180° C. to obtain a composite material;

[0075] The preparation method of modified carbon fiber is as follows:

[0076] Step (1): 8 parts of carbon fiber are placed in 320 parts of acetone, extracted for 48 hours, and after washing and drying, a pretreated carbon fiber is obtained;

[0077] Step (2): adjusting 500 parts of 0.01 mol / L Tris-HCl buffer to pH=8.5, adding 1 part of dopamine hydrochloride and 2 parts of polyethyleneimine and mixing evenly, then adding 8 parts of pretreated carbon fiber and mixing evenly, reacting for 24 hours, washing and drying, and obtaining amino carbon fiber;

[0078] Step (3): Under nitrogen protection, 16 parts of trimethylolpropane triglycidyl ether, 24 parts of 2,2'-diallyl bisphenol A and 4.8 parts of tetrabutylammonium bromide are mixed evenly, reacted at 85°C for 24 hours, cooled to room temperature, dissolved, layered, rotary evaporated and dried to obtain a hyperbranched epoxy resin;

[0079] Step (4): 8 parts of amino carbon fiber and 16 parts of hyperbranched epoxy resin were mixed evenly, and reacted at 40° C. for 10 hours to obtain modified carbon fiber;

[0080] The preparation method of the heat-resistant agent is as follows:

[0081] 7 parts of L-cysteine, 12.6 parts of 1,2,4-cyclohexanetricarboxylic anhydride and 350 parts of glacial acetic acid were mixed evenly, stirred at room temperature for 24 hours, heated to 120°C and refluxed for reaction for 6 hours, and distilled under reduced pressure, washed and dried to obtain an intermediate; 7 parts of the intermediate, 10.5 parts of 2-bis[4-(4-aminophenoxy)phenyl]propane and 15.4 parts of tetrabutylammonium bromide were mixed evenly, heated to 70°C, 34.5 parts of triphenyl phosphite and 21 parts of aniline were added, and the temperature was continued to be raised to 120°C, reacted for 2 hours, and a heat-resistant agent was obtained after precipitation, filtration and drying;

[0082] An application of a composite material for a lightweight rail transit bridge comprises the following steps: feeding the composite material into an injection molding machine, melting it at 175°C, injecting it into a mold (mold temperature 185°C, mold pressure 30Mpa), cooling it, and obtaining a lightweight rail transit bridge.

[0083] Comparative Example 1: A molding process of a composite material for a lightweight rail transit bridge, comprising the following processes:

[0084] Compared with Example 2, in Comparative Example 1, the modified carbon fiber in step S1 is replaced with carbon fiber of the same mass, and the other steps are the same as those in Example 2.

[0085] Comparative Example 2: A molding process of a composite material for a lightweight rail transit bridge, comprising the following processes:

[0086] Compared with Example 2, the composite of Comparative Example 2 includes the following components by weight: 5 parts of modified carbon fiber, 1 part of heat-resistant agent, and 0.8 parts of photoinitiator. Other steps are the same as those of Example 2.

[0087] Comparative Example 3: A molding process of a composite material for a lightweight rail transit bridge, comprising the following processes:

[0088] Compared with Example 2, the composite of Comparative Example 3 includes the following components by weight: 1 part of modified carbon fiber, 5 parts of heat-resistant agent, and 0.8 parts of photoinitiator. Other steps are the same as those in Example 2.

[0089] Comparative Example 4: A molding process of a composite material for a lightweight rail transit bridge, comprising the following processes:

[0090] The preparation method of modified carbon fiber is as follows:

[0091] Step (1): 5 parts of carbon fiber are placed in 150 parts of acetone, extracted for 46 hours, and after washing and drying, a pretreated carbon fiber is obtained;

[0092] Step (2): adjusting 280 parts of 0.01 mol / L Tris-HCl buffer to pH=8.5, adding 0.7 parts of dopamine hydrochloride and 1 part of polyethyleneimine and mixing evenly, then adding 5 parts of pretreated carbon fiber and mixing evenly, reacting for 23 hours, washing and drying, and obtaining amino carbon fiber;

[0093] Step (3): Under nitrogen protection, 8 parts of trimethylolpropane triglycidyl ether, 10 parts of 2,2'-diallyl bisphenol A and 1.6 parts of tetrabutylammonium bromide are mixed evenly, reacted at 80°C for 23 hours, cooled to room temperature, dissolved, layered, rotary evaporated and dried to obtain a hyperbranched epoxy resin;

[0094] Step (4): 5 parts of amino carbon fiber and 2.5 parts of hyperbranched epoxy resin were mixed evenly, and reacted at 35° C. for 9 hours to obtain modified carbon fiber;

[0095] Compared with Example 2, in step (4) of Comparative Example 4, the mass ratio of the amino carbon fiber to the hyperbranched epoxy resin is 1:0.5, and the other steps are the same as those in Example 2.

[0096] Experiment: The lightweight rail transit bridges obtained in Examples 1-3 and Comparative Examples 1-4 were used to prepare samples, and their performance was tested and the test results were recorded:

[0097] The Vicat softening temperature (VST) was determined according to GB / T 1633-2000 standard. A Vicat softening point temperature tester was used for the test. The sample size was 10 mm × 10 mm × 3 mm. The heating rate was 120 °C / h. The temperature when the needle was pressed into 1 mm was the Vicat softening temperature.

[0098] The bending strength was measured according to GB / T 9341-2008 standard, the sample size was 80 mm × 10 mm × 4 mm, and the test speed was 2 mm / min.

[0099] Test Results

[0100] Vicat softening temperature(℃) Bending strength(Mpa) Example 1 104.8 146 Example 2 108.2 150 Example 3 106.5 148 Comparative Example 1 95.7 132 Comparative Example 2 85.2 139 Comparative Example 3 89.4 124 Comparative Example 4 100.6 143

[0101] According to the data in the above table, we can clearly draw the following conclusions:

[0102] 1. Compared with Examples 1-3, the Vicat softening temperature and flexural strength of the product obtained in Comparative Example 1 are both reduced, indicating that the modified carbon fiber prepared by the present invention has better stability and toughness than carbon fiber, and can be combined with a heat-resistant agent to further enhance the performance of the composite material.

[0103] 2. Compared with Examples 1-3, the Vicat softening temperature and flexural strength of the products obtained in Comparative Examples 2 and 3 are both reduced, which indicates that the performance of the composite prepared by the present invention is affected by its component ratio. The ratio of the heat-resistant agent to the modified carbon fiber in the components is directly related to the mechanical properties and thermal stability of the composite material. Therefore, by selecting a component ratio within an appropriate range, a composite material with better performance can be prepared.

[0104] 3. Compared with Examples 1-3, the Vicat softening temperature and flexural strength of the product obtained in Comparative Example 4 are both reduced. It can be seen that when the amount of hyperbranched epoxy resin added is reduced, the interfacial bonding strength between the carbon fiber and the heat-resistant agent will be affected, thereby affecting the overall strength and rigidity of the material.

[0105] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A molding process of a composite material for a lightweight rail transit bridge, characterized in that: The steps include: Step S1: uniformly mixing the modified carbon fiber, the heat-resistant agent and the photoinitiator, and irradiating the mixture with ultraviolet light to obtain a composite; Step S2: uniformly mixing the polyvinyl chloride resin, acrylonitrile-butadiene-styrene copolymer, the compound, the plasticizer, the antioxidant, the stabilizer, and the lubricant, and performing internal mixing in an internal mixer at a temperature of 165-175° C. to obtain a blend; Step S3: adding the blend obtained in S2 into a twin-screw extruder for extrusion granulation to obtain a composite material.

2. The molding process of a composite material for a lightweight rail transit bridge according to claim 1, characterized in that: In the step S1, the composite comprises the following components by weight: 3-8 parts of modified carbon fiber, 2-7 parts of heat-resistant agent, and 0.5-1.0 parts of photoinitiator.

3. The molding process of a composite material for a lightweight rail transit bridge according to claim 2, characterized in that: The preparation method of the modified carbon fiber is as follows: Step (1): placing the carbon fiber in acetone, extracting for 44-48 hours, washing and drying to obtain pretreated carbon fiber; Step (2): adjust the pH of Tris-HCl buffer to 8.5, add dopamine hydrochloride and polyethyleneimine and mix evenly, then add pretreated carbon fiber and mix evenly, react for 22-24 hours, wash and dry to obtain amino carbon fiber; Step (3): under nitrogen protection, trimethylolpropane triglycidyl ether, 2,2'-diallyl bisphenol A and tetrabutylammonium bromide are uniformly mixed, reacted at 75-85° C. for 22-24 hours, cooled to room temperature, dissolved, layered, rotary evaporated and dried to obtain a hyperbranched epoxy resin; Step (4): Evenly mix the amino carbon fiber and the hyperbranched epoxy resin, and react at 30-40° C. for 8-10 hours to obtain modified carbon fiber.

4. The molding process of a composite material for a lightweight rail transit bridge according to claim 2, characterized in that: The preparation method of the heat-resistant agent is as follows: Mix L-cysteine, 1,2,4-cyclohexanetricarboxylic anhydride and glacial acetic acid evenly, stir at room temperature for 22-24 hours, heat to 110-120°C and reflux for reaction for 4-6 hours, and obtain an intermediate after vacuum distillation, washing and drying; mix the intermediate, 2-bis[4-(4-aminophenoxy)phenyl]propane and tetrabutylammonium bromide evenly, heat to 50-70°C, add triphenyl phosphite and aniline, continue to heat to 110-120°C, react for 1-2 hours, and obtain a heat-resistant agent after precipitation, filtration and drying.

5. The molding process of a composite material for a lightweight rail transit bridge according to claim 1, characterized in that: The composite material comprises the following components by weight: 80-100 parts of polyvinyl chloride resin, 10-20 parts of acrylonitrile-butadiene-styrene copolymer, 5-15 parts of compound, 2-10 parts of plasticizer, 0.2-0.5 parts of antioxidant, 5-15 parts of stabilizer and 0.5-1.0 parts of lubricant.

6. The molding process of a composite material for a lightweight rail transit bridge according to claim 5, characterized in that: The plasticizer is dioctyl phthalate.

7. The molding process of a composite material for a lightweight rail transit bridge according to claim 1, characterized in that: The antioxidant is antioxidant 1010.

8. The molding process of a composite material for a lightweight rail transit bridge according to claim 1, characterized in that: The stabilizer is a composite calcium zinc stabilizer.

9. A composite material for a lightweight rail transit bridge frame obtained by the molding process according to any one of claims 1 to 8.

10. An application of the composite material for lightweight rail transit bridge according to claim 9, characterized in that: The method comprises the following steps: feeding the composite material into an injection molding machine, melting the composite material at 165-175° C., injecting the composite material into a mold, and cooling the mold to obtain a lightweight rail transit bridge frame.